Assessing the Performance of Smart Inverter Functionalities in PV-Rich LV Distribution Networks - Almeida D.; Pasupuleti J.; Ekanayake J. (Institute of Electrical and Electronics Engineers Inc., 2023)
The overvoltage issue has been deemed as a significant technical challenge owing to the high integration of solar photovoltaic (PV) systems into the low voltage (LV) distribution networks. As a promising solution to this problem, smart inverter controls have gained attention in facilitating localized voltage control. In this paper, the effectiveness of three smart inverter functionalities namely; Volt-Var, Volt-Watt, and simultaneous Volt-Var and Volt-Watt controls have been analyzed and quantified in terms of multiple performance criterion. A detailed analysis has been conducted using a generic, Malaysian LV distribution network in order to demonstrate the applicability of adopting smart inverter controls in alleviating overvoltage issues in PV-rich LV networks. Results reveal that the usage of smart inverter controls help to mitigate overvoltage issues and support network operation conditions. Further, the results highlight the importance of selecting the most suitable control technique for a better network performance. 2020 IEEE.